Mitochondria dysfunction in lung cancer-induced muscle wasting in C2C12 myotubes - McLean, Julie B.; Moylan, Jennifer S.; Andrade, Francisco H. (Frontiers in Physiology, 2014)
Aims: Cancer cachexia is a syndrome which results in severe loss of muscle mass and marked fatigue. Conditioned media from cachexia-inducing cancer cells triggers metabolic dysfunction in skeletal muscle, including decreased mitochondrial respiration, which may contribute to fatigue. We hypothesized that Lewis lung carcinoma conditioned medium (LCM) would impair the mitochondrial electron transport chain (ETC) and increase production of reactive oxygen species, ultimately leading to decreased mitochondrial respiration. We incubated C2C12 myotubes with LCM for 30 minutes, 2hrs, 4hrs, 24hrs or 48hrs. We measured protein content by western blot; oxidant production by 2′,7′-dichlorofluorescin diacetate (DCF), 4-amino-5-methylamino-2',7'-difluorofluorescein diacetate (DAF), and MitoSox; cytochrome c oxidase activity by oxidation of cytochrome c substrate; and oxygen consumption rate (OCR) of intact myotubes by Seahorse XF Analyzer. Results: LCM treatment for 2hrs or 24hrs decreased basal OCR and ATP-related OCR, but did not alter the content of mitochondrial complexes I, III, IV and V. LCM treatment caused a transient rise in reactive oxygen species (ROS). In particular, mitochondrial superoxide (MitoSOX) was elevated at 2hrs. 4-Hydroxynonenal, a marker of oxidative stress, was elevated in both cytosolic and mitochondrial fractions of cell lysates after LCM treatment. Conclusion: These data show that lung cancer-conditioned media alters electron flow in the ETC and increases mitochondrial ROS production, both of which may ultimately impair aerobic metabolism and decrease muscle endurance.